2020
DOI: 10.1101/2020.05.07.082990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleoid openness profiling links bacterial genome structure to phenotype

Abstract: 14Gene expression requires specific structural alternations in the nucleoid structure to enable the access 15 of the transcription machinery into the genomic DNA. In prokaryotes, DNA binding proteins, 16including nucleoid-associated proteins (NAPs) and transcription factors (TFs), drive the change in 17 structure and gene expression. Currently, studies of global NAP and TF binding are often hindered by 18 the lack of appropriate epigenomic tools. Here, we present POP-seq, a method that provides in vivo 19 geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We have demonstrated that IPOD-HR simultaneously enables resolution of individual changes in TF binding at specific sites, inference of PLOS BIOLOGY new regulatory motifs that likely correspond to functional but poorly characterized transcriptional regulators, and large-scale patterns of protein occupancy indicative of constitutively silenced genomic regions. IPOD-HR thus falls into the same family as methods such as DNase I hypersensitivity [45], micrococcal nuclease digestion with deep sequencing (MAU : PleasenotethatMN Nase-seq) [46], and ATAC-seq [39], but was from its inception developed, tuned, and validated for the unique molecular and biophysical features of bacterial chromosomes (we note that applications of ATAC-like methods to bacteria have recently been reported in preprints [47,48] postdating the original preprint of the present manuscript [49]).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that IPOD-HR simultaneously enables resolution of individual changes in TF binding at specific sites, inference of PLOS BIOLOGY new regulatory motifs that likely correspond to functional but poorly characterized transcriptional regulators, and large-scale patterns of protein occupancy indicative of constitutively silenced genomic regions. IPOD-HR thus falls into the same family as methods such as DNase I hypersensitivity [45], micrococcal nuclease digestion with deep sequencing (MAU : PleasenotethatMN Nase-seq) [46], and ATAC-seq [39], but was from its inception developed, tuned, and validated for the unique molecular and biophysical features of bacterial chromosomes (we note that applications of ATAC-like methods to bacteria have recently been reported in preprints [47,48] postdating the original preprint of the present manuscript [49]).…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that IPOD-HR simultaneously enables resolution of individual changes in transcription factor binding at specific sites, inference of new regulatory motifs which likely correspond to functional but poorly characterized transcriptional regulators, and large-scale patterns of protein occupancy indicative of constitutively silenced genomic regions. IPOD-HR thus falls into the same family as methods such as DNase I hypersensitivity [43], MNase-seq [44], and ATAC-seq [37], but was from its inception developed, tuned, and validated for the unique molecular and biophysical features of bacterial chromosomes (we note that applications of ATAC-like methods to bacteria have recently been reported in preprints [45,46] post-dating the preprint of the present manuscript [47]).…”
Section: Discussionmentioning
confidence: 99%